Julia 1. 0 Programming Complete Reference Guide Discover Julia, a High-Performance Language for Technical Computing - Balbaert, Ivo (Packt Publishing, Limited, 2019)
This Learning Path is your step-by-step guide to learn the high-level and high-performance Julia language and build simple-to-advanced applications with it using modern tools. Through multiple projects and examples, you'll learn work with powerful open-source libraries for data wrangling, analysis, and visualization and build full-featured ...